2020
DOI: 10.1093/aob/mcaa058
|View full text |Cite
|
Sign up to set email alerts
|

Pollen adaptation to ant pollination: a case study from the Proteaceae

Abstract: Background and Aims Ant–plant associations are widely diverse and distributed throughout the world, leading to antagonistic and/or mutualistic interactions. Ant pollination is a rare mutualistic association and reports of ants as effective pollinators are limited to a few studies. Conospermum (Proteaceae) is an insect-pollinated genus well represented in the south-western Australia biodiversity hotspot, and here we aimed to evaluate the role of ants as pollinators of C. undulatum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 54 publications
1
16
0
2
Order By: Relevance
“…Metapleural glands are an ant innovation that has been lost repeatedly and is absent in Camponotus (Yek and Mueller, 2011), the most abundant visitors of E. triandra. Indeed, Camponotus ants in our study did not reduce pollen germinability, in agreement with results reported for other Camponotus species (Delnevo et al, 2020, but see de Vega et al, 2009, for a counterexample) including in E. foeminea, where an actual increase in pollen germinability was observed after contact with these ants (Bolinder et al, 2016). Moreover, species of Camponotus have been frequently associated with pollination in dry habitats (de Vega et al, 2014;Del-Claro et al, 2019).…”
Section: Ant Species-specific Traits Promote Pollinationsupporting
confidence: 93%
See 1 more Smart Citation
“…Metapleural glands are an ant innovation that has been lost repeatedly and is absent in Camponotus (Yek and Mueller, 2011), the most abundant visitors of E. triandra. Indeed, Camponotus ants in our study did not reduce pollen germinability, in agreement with results reported for other Camponotus species (Delnevo et al, 2020, but see de Vega et al, 2009, for a counterexample) including in E. foeminea, where an actual increase in pollen germinability was observed after contact with these ants (Bolinder et al, 2016). Moreover, species of Camponotus have been frequently associated with pollination in dry habitats (de Vega et al, 2014;Del-Claro et al, 2019).…”
Section: Ant Species-specific Traits Promote Pollinationsupporting
confidence: 93%
“…The most widespread form of ant-plant mutualistic interactions are defensive mutualisms, where ants consume extrafloral nectar (EFN) and protect plants from herbivores (Marazzi et al, 2013). Ant pollination, where floral nectar is offered as a reward in exchange for the pollination service, is rarer (e.g., Peakall and Beattie, 1991;Del-Claro et al, 2019;Delnevo et al, 2020). On the one hand, ants have been traditionally considered poor pollinators because of the presence of metapleural gland secretions on their integument that negatively affect pollen viability (Beattie et al, 1984) and due to their limited movement, since wingless foragers only visit resources near their nest (Faegri and van der Pijl, 1979;Domingos-Melo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While ants were clearly the most abundant visitors to the nipa flowers at MBC, until recently their role as pollinator has been downplayed in the scientific literature. Ants produce an J Poll Ecol 27(5) antimicrobial secretion that can reduce pollen viability (Beattie et al 1985), and this negative role in pollination has been widely assumed to be the norm until recently, as a growing number of studies have demonstrated effective pollination by ant species in some plants (Hickman 1974;Rostás & Tautz 2011;De Vega & Gomez 2014;Domingos-Melo et al 2017;Delnevo et al 2020). The ant species found on our nipa palms, Paratrechina longicornis, is widespread in the U.S. and does not appear to be a newcomer to South Florida.…”
Section: Discussionmentioning
confidence: 99%
“…As a recent example of mutually beneficial relationships, Conospermum, a plant that has developed a way to use ants to its advantage, like the pollinators overcoming their antimicrobial defenses, a mechanism as effective as the action of native bees! (Stock et al, 2020) [57]. This is the first finding of such a cooperation mechanism, even if "it would be risky, in an evolutionary sense, for the plant to rely only on the native bee for pollination" say the authors.…”
Section: The Evolutionary Taxonomy Of Cognitive Controlmentioning
confidence: 94%